Teachers' Needs and Professional Development: A Systematic Review - Haemin Kim; Keith M. Graham (Universidad de La Sabana, 2022)
This study utilizes a systematic review process to synthesize research on content and language integrated learning (CLIL) teachers' self-reported needs and professional development. In order to draw connections between these two areas of research and highlight gaps, this study adopted a framework composed of seven competences: linguistic, pedagogical, scientific knowledge, organizational, interpersonal, collaborative, and reflective. Six electronic databases were used, and a forward and backward search was conducted. After considering inclusion criteria, 43 articles were included, with 33 studies for teachers' needs, nine for professional development, and one for accounting for both. The findings of the review showcase that not all competences have received equal coverage in the literature. In some cases, teachers' reported needs within a competence were not addressed in the professional development literature. Further, the reports of many competences seem to be general, suggesting future work may need to examine each competence in more depth.